Plan de marketing para la Cooperativa de Ahorro y Crédito "TEXTIL 14 DE MARZO", en la ciudad de Santo Domingo de los Tsáchilas, año 2014. - Castro Alava, Rody Ubaldo (2015)
The Ecuador is a country where many credit unions occupy a percentage of 27.6%, currently presenting an economy with serious social problems due to the various crises that has kept the country for several years, it is for this reason that there is considers very important the cooperative as it is an economic system and establishing a source of progress for the country's economic development. The credit union "Textile March 14" is little known in local market, it is for this reason that you should make strategies and repositioning of the brand in order to become one of the best cooperatives in the city and is located in the following address: CLL. May 29 and San Gabriel of the canton of Santo Domingo, Santo Domingo Province of Tsáchilas. The marketing plan is of great need for the cooperative and to reposition the company, obtaining greater customer loyalty orderly projected into the future based on strategies in the short, medium and long term, it also allows the current situation, interest Customer institution by market analyzes and competition and to generate new ideas a positive image and quality of the services provided by the cooperative to all its customers. Therefore the credit union "Textile March 14" has decided to form part of a marketing plan with the necessary strategies to maintain and increase their customers, and excel in business in the canton of Santo Domingo